A novel endoscopic hydro-mastoidectomy technique for transcanal endoscopic ear surgery. Issue 3 (March 2019) - Nishiike, S; Oshima, K; Imai, T; Uetsuka, S
Abstract: Background: In order to remove a cholesteatoma in the mastoid under transcanal endoscopic ear surgery, it is necessary to perform transcanal endoscopic mastoidectomy. Bone dust and blood, however, obscure the surgical field. A novel endoscopic hydro-mastoidectomy technique was developed, in which the operator performs the mastoidectomy 'underwater' using a lens cleaning system that provides saline perfusion in the surgical space. Methods: A curved round coarse diamond bur is attached to an otological drill. A lens cleaning sheath is fitted to the endoscope. The surgeon controls the infusion of saline solution by stepping on a footswitch of the power console. Results: Endoscopic hydro-mastoidectomy washes out bone dust and blood from the surgical field, improving the surgical view during mastoidectomy. Additionally, the operator can easily control the flow of saline perfusion. Conclusion: This technique provides a clear surgical view by washing out bone dust and blood from the surgical area. The setup for endoscopic hydro-mastoidectomy technique is easy and the operator needs only to buy sheaths if they already own the power console, as many otological and rhinological surgeons do.